Awareness, Knowledge, Attitude, and Practice of Patient Safety Culture Among Healthcare Providers and Managers in a Tertiary Healthcare Hospital - Murtaza, Hina; Lal, Chooni; Kumari, Darshana; Gova, Murtaza Ali (Biological and Clinical Sciences Research Journal, 2025)
Patient safety culture is a cornerstone of quality healthcare delivery, yet unsafe practices, communication failures, and systemic barriers continue to compromise outcomes. Objective: To assess the awareness, knowledge, attitude, and practice of patient safety culture among healthcare providers and managers in a tertiary healthcare hospital, using the Hospital Survey on Patient Safety Culture (HSOPSC). Methods: This descriptive cross-sectional study was conducted at the Jinnah Postgraduate Medical Center and the National Institute of Child Health from January 2023 to September 2023. A total of 375 participants, including doctors, nurses, allied health professionals, and managers, were enrolled through non-probability consecutive sampling. Data were collected using a structured, pre-tested questionnaire that incorporated the HSOPSC, developed by the Agency for Healthcare Research and Quality (AHRQ). Domains assessed included awareness, knowledge, attitudes, practices, event reporting, and safety ratings. Results: Most participants demonstrated high awareness (68.0%) and knowledge (61.6%) of patient safety culture. Positive attitudes were reported by 70.1% of respondents, with teamwork (77.1%) and communication openness (66.1%) being rated as the highest. However, non-punitive responses to errors (52.5%), staffing adequacy (49.9%), and handoffs and transitions (44.8%) were identified as areas for improvement. Event reporting was limited, with 51.2% reporting no events in the past three months, and 64.8% rated their work units as excellent or very good. Knowledge of patient safety SOPs and awareness of safety unit availability were significantly associated with more positive perceptions of safety culture (p < 0.05). Conclusion: The study highlights that while awareness and attitudes toward patient safety culture are generally favorable, systemic barriers, particularly underreporting of events, fear of blame, inadequate staffing, and limited knowledge of global frameworks, persist as significant challenges to improving patient safety culture.